A STUDY OF EFFECT OF GENDER AND AGE ON TEACHERS’ ATTITUDE, COMPETENCIES AND SELF-EFFICACY BELIEFS - Ragho, Baviskar Chandrakant; Kachave, Dhananjay Shrimantrao (ShodhKosh: Journal of Visual and Performing Arts, 2023)
The purpose of this study was to explore the effect of Gender and Age on TAS, TCS, and TSEBS Factors perceived by secondary school teachers’. The sample (N=367) of the study were selected from teachers working in Southern region of Rayat Shikshan Sanstha. Seven points Likert type Teachers’ Attitude Scale (TAS), Teachers’ Competencies Scale (TCS), Teachers’ Self-efficacy Beliefs Scale (TSEBS) were developed with Demographic information to collect the data. The collected data has been analyzed by applying One –way MANOVA and Pearson ‘r’ and ‘F’ test. The overall MANOVA of effect of Gender and Age factors summary on TAS, TCS, TSEBS and the value of Wilks Lambda of Gender is 0.919 with 3 and 355 degrees of freedom is equivalent to an F ratio of 10.368 with P= 0.000 and the value of Wilks Lambda of Age is 0.972 with 12 and 940 degrees of freedom is equivalent to an F ratio of 0.838 with P= 0.611 and the value of Wilks Lambda of Gender*Age is 0.967 with 12 and 940 degrees of freedom is equivalent to an F ratio of 1.005 with P= 0.442. Thus, the null hypothesis is rejected. The difference for F (9, 357) ratio is found significant on TAFT, TSEBFT and not significant difference found on TCFT at 0.05 levels. The significant effect of Gender for F (1, 4) ratio is found on TAFT, TSEBFT and not significant effect found on TCFT at 0.05 levels. Not significant effect of Age for F (1, 4) ratio is found on TAFT, TSEBFT at 0.05 levels and Not significant effect of Gender*Age for F (1, 4) ratio is found TAFT, TSEBFT at 0.05 levels.